Transformation of the spectrum of coupled nonlinear oscillators during transition to the chaotic dynamic - Syaber, S.S.; Anisimov, I.O. (Вопросы атомной науки и техники, 2014)
Transition to the chaotic dynamic in the system of two coupled conservative nonlinear oscillators has been studied. Oscillators are represented by conservative LC circuits with nonlinear capacitors. The system exhibits chaotic behavior in some range of initial conditions. We focus on the spectra analysis of the oscillations that correspond to qualitatively different phase trajectories. Certain correspondence with the signal modulation has been found.